Problems of domestic school natural science education, patriotism promotion and their influence on the training of medical professionals - N. A. Bogdanov; A. P. Aniskina (Кардиоваскулярная терапия и профилактика)
Aim. To identify problems of domestic natural science education and patriotism promotion (as a motivational personality component), which negatively affect the professional training of health professionals.Material and methods. When working on the article, we used the following methods: theoretical — analysis of modern legal documents of secondary general education, analysis of recommended educational literature on subjects, and empirical — analysis of the experience of biology teachers in modern conditions according to the recommended programs of disciplines and standards; analysis of the results of the Unified State Exam (USE) for 2021-2022 and scientific generalization.Results. An analysis of the main problems of natural science education at the present time is presented. The authors consider the most significant of them to be a change in the content of school education, an unacceptable reduction in hours for natural science disciplines, ignoring the domestic tradition and didactic principles of science and systematization, practical experience accumulated by domestic teachers and methodologists in the preparation of programs and textbooks. The reasons for the lack of special knowledge and objective thinking in a large part of students are considered, which is confirmed by the USE for the period 2015-2022. It is pointed out that it is practically impossible to carry out a systematic mastering of the content of an educational subject and the development of mental skills, based on modern textbooks. The combination of these problems has led to a decrease in the development and educational potential of the natural sciences and the quality of education in general.Conclusion. The article suggests possible ways to overcome this undesirable trend, substantiates the need to rethink the importance of school science education as a resource for the development of science, the national economy, medicine and the defense industry. There is a need to create an "image of the future" among students as a system-forming factor in the social and cultural development of Russian society.